(untitled) (Pedagogy of Higher and Secondary Education, 2022)
Article is devoted ta the actual problem of the formation of culural paradigm of the teacher. Leading role in this process, according to the authors, is methodical association class masters, which is designed to equip teacher-educaor achievements of modern theon ond practice of healthy individual student.